Risk Consulting in Public Administration: Evidences of Insurance Brokers in the Emilia-Romagna Municipalities - Vincenzo Riso; Monia Castellini (European Scientific Journal, ESJ, 2019)
Over the past years, risk management has been embedded in all public administration and scholars have asserted the need to improve the research about it. This paper aims to understand if an insurance broker has a role in the public administration risk management system, analysing the relationship between the operational risk management activities and control systems in the public administration and the evolution of the insurance broker as a risk consultant. Finally, through a content analysis, this study presents an observation about 331 municipalities from the Emilia-Romagna to understand how many municipalities can have an insurance broker as a partner.